Employee’s productivity at the operation of indonesian railway - Muhammad Alkirom Wildan (STIE Perbanas Surabaya, 2020)
This research was done to study the effect of the physical work environment and nonphysical workplace environment on employee’s productivity. It was conducted at the Indonesian Railway Corp. operation district 8. The population consists of 250 employees and the sample was determined using Slovin’s equation with the size 71 employees. The data was taken using a questionnaire and analyzed using linear regression to analyze the partial and simultaneous effect of the physical work envi-ronment and nonphysical workplace environment towards employee’s productivity. Based on the statistical analysis conducted using SPSS 18, the p-Value of the physical workplace environment and nonphysical workplace environment are 0.013 and 0.036 respectively, both are less than 0.05. Thus, it indicates that the physical workplace environment and nonphysical workplace environment significantly and partially affect employee’s productivity, while the F-count is 14.831 and its p-Value is 0.000 (<0.05) indicating that physical workplace environment and non-physical workplace environment simultaneously affected employee’s productivity. The regression coefficient (R2) was 0.504 or 50.4 %. Therefore, it also shows that the physical workplace environment and non-physical workplace environment simultaneously affected employee’s productivity about 50.4%, and about 49.6% might be affected by other variables.